Familial ectrodactyly: a rare report of lobster-claw in a Malay family - K.A, Nur Ayuni; I, Imma Isniza; L, Rahul; Faa’iza, Naadira; A, Nur Syahirah (Diyarbakir: Ektodermal Displazi Grubu-Türkiye, 2021)
We describe a case of ectrodactyly in isolated non-syndromic form claw in three living generation of a Malay family which presented as autosomal dominant pattern of inheritance with sporadic occurrence. To our knowledge, this is the first report of such case in Malaysia. A three-year-old boy with claw toes presented to Paediatric Orthopaedic Unit accompanied by his mother and grandfather. He is an active child with normal intellectual. Neither facial dysmorphism nor cleft lip and palate was observed. His right tibia is shorter than the left one and his ankle is totally dislocated posteriorly. His right foot has only one ray and his right ankle joint is in 100’ equinus. For his left lower limb, the leg and ankle are normal. However, the left foot is bifid with two lateral and one medial ray. He can walk on the stump of distal right ankle but with short limb gait. He prefers to walk in kneeling position as he finds it a bit faster and that he can move freely. Other systemic reviews are unremarkable. His mother was born with the similar deformity on the feet and ankle. She underwent below knee amputation at the age of 6 and has been using prosthesis since after corrective surgery failed. The grandfather has central splits in both hands and bifid femur bilaterally. Only one ray present on each foot. The prognosis for most people with ectrodactyly syndrome is very good. Various cosmetic prosthesis, amputation or reconstructive surgery might help, depending on the type of deformity and as per case basis. Multidisciplinary care would contribute significantly to improve the survival and the quality of life of a child with congenital musculoskeletal malformations such as ectrodactyly.